Perception et représentation de l’univers amazonien dans Sortilèges de Diana Lichy : un paysage chamanique - Cécile Bertin-Elisabeth (VertigO)
Diana Lichy, a modern Venezuelan poetess, depicts a shamanic landscape in her anthology entitled Spells (1994) as a landscape particular to the imaginative world and traditions of the Amazonian universe. These thirty poems are as many dreamlike "trips" into irrational worlds in which, unlike the western way privileging the look, the multi-sensory dimension focuses on sonorous timeless landscapes seen from inside and deprived of exoticism. Thus, through metamorphic games Diana Lichy leads us to the discovery of Amerindian rather than Amazonian landscapes since the Amazonian landscape does not exist unless it is looked at. Being a world representation, as occurring here, her depiction of the Amerindian imaginative world is endowed with a specific conception of the universe, of men and their relationships.